The new additive era of orthodontics: 3D-printed aligners and shape memory polymers—the latest trend—and their environmental implications - Amani Alkhamees (Journal of Orthodontic Science)
The era of printed aligners has just began in the orthodontic field. Orthodontists have become more interested in 3D-printed in-office aligners. Treatment due to this technology can become faster and more efficient. Advantages highlighted by newly introduced materials for manufacturing processes of 3D aligners present the possibility of overcoming limitations faced by thermoformed aligners, making them a potential replacement of thermoformed aligner. Advances in aligner material, especially shape memory polymers, have the potential to bring about radical transformations in the clinical applications of clear aligner therapy. Safety and cytotoxicity of printable resins along with its mechanical properties must be scientifically studied extensively before it is cleared for clinical use. In addition, with the increased use of aligners, awareness of the environmental burden of plastic waste should be emphasized. Attention should be directed into the development of recyclable materials for aligners along with establishing clear recycling guidelines and patient education programs on proper recycling methods. With the introduction of Graphy’s clear biocompatible photocurable resin, which is equipped with a shape–memory function and is printed in an environmental friendly way by reducing carbon emissions. Direct 3D printing represents the future of clear aligner therapy, and more studies to test these new technologies and materials are required.